Smoking marijuana and 9- tetrahydrocannabinol (THC) (dronabinol, Marinol) is used for treating anorexia and weight loss caused by the human immunodeficiency virus-1 (HTV-1). However, there have been concerns that these chemicals may have a negative in (International Journal of Innovative Research in Engineering & Management, 2023)
Smoking marijuana and 9- tetrahydrocannabinol (THC) (dronabinol, Marinol) is used  for treating anorexia and weight loss caused by the human  immunodeficiency virus-1 (HTV-1). However, there have  been concerns that these chemicals may have a negative  influence on the immune systems of HTV-infected persons.  The writer has conducted randomised, potential, controlled  trial in adults who have HIV-infection and who have been  receiving protease inhibitor-that contains high active  antiretroviral therapy to assess the usage of marijuana  cigarette (3.95 percent THC), dronabinol (2.5 mg), and an  oral placebo in adults who have HIV-infection receiving  protease inhibitor-containing highly active antiretroviral  therapy (HAART). Immunological presentation (flow  cytometric quantification of cellular subpopulations, B  cells, and natural killer [NK] cells) and immunological  function (induced cytokine production, NK cell activity,  and lymphoproliferation) tests were carried out at the  beginning and on a regular basis.
Keywords: Cannabinoids; Cells; Marijuana; HIV; Δ9- tetrahydrocannabinol (THC).